2021
DOI: 10.1089/vio.2020.0043
|View full text |Cite
|
Sign up to set email alerts
|

Response to Domestic Violence During the COVID-19 Outbreak in Japan

Abstract: Domestic violence (DV) incidents, triggered as a result of coronavirus disease 2019 (COVID-19) imposed lockdowns, are being increasingly reported worldwide. In April 2020, the Spousal Violence Counseling and Support Centers conducted 13,272 DV consultations, which was 1.3 times higher than the number in April 2019. The All Japan Women's Shelter Network, a group of private shelters, responded to the DV problems resulting from COVID-19 and submitted a petition to the Japanese government on March 30, 2020. This l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Stay‐at‐home measures have resulted in an increase in domestic violence both globally and in Japan (Suga, 2020). The United Nations has referred to domestic violence in the era of COVID‐19 as a ‘shadow pandemic’ (Mlambo‐Nguka, 2020).…”
Section: Impact Of the Pandemic On Families In Japanmentioning
confidence: 99%
See 1 more Smart Citation
“…Stay‐at‐home measures have resulted in an increase in domestic violence both globally and in Japan (Suga, 2020). The United Nations has referred to domestic violence in the era of COVID‐19 as a ‘shadow pandemic’ (Mlambo‐Nguka, 2020).…”
Section: Impact Of the Pandemic On Families In Japanmentioning
confidence: 99%
“…In Japan, as the pandemic unfolded, there was an increase in the number of consultations for domestic violence. In Spring 2020, the All Japan Women’s Shelter Network, an umbrella organisation of domestic violence services, urged the government to increase support for victims of domestic violence (Suga, 2020). In response, in April 2020, the Japanese government set up a 24‐hour domestic violence hotline in 10 different languages (Cabinet Secretariat & Gender Equality Bureau Cabinet Office, 2020a).…”
Section: Impact Of the Pandemic On Families In Japanmentioning
confidence: 99%
“… 10 11 Financial hardships, increased threats to physical health coupled with their daily responsibilities have made people more violent and aggressive. 12 While hotlines have been receiving complaints of domestic violence, 13 14 multiple instances of abuse were also seen outside the closed room among general people. Some instances include abusing health workers for spreading COVID-19, 15 abusing people for not wearing masks, 16 17 for not being able to pay room rents, 18 etc.…”
Section: Introductionmentioning
confidence: 99%
“…It has been revealed that the pandemic has significantly impacted Japanese people not only economically but also in many aspects of social life, particularly mental and physical health (Tanoue et al, 2020;Ueda et al, 2020;Nagasu et al, 2021;Makizako et al, 2021), human rights (Matsuda et al, 2021;MARTIN, 2021), domestic violence (Suga, 2021;Suga 2021a), economic insecurity and reduction of purchasing power (McIntyre & Lee, 2020;Kobayashi et al, 2021;Tsurugano et al, 2021;Yatsuya&Ishitake, 2021), education, leisure and recreation (Usami et al, 2021;Yamamura &Tsustsui, 2021;Tahara et al, 2021), suicide (Osaki et al, 2021;Nomura et al, 2021). However, seemingly minor academic works have been conducted to understand the length and breadth of the impact of Covid-19 in the social life of the Japanese people.…”
Section: Introductionmentioning
confidence: 99%